Glycosyl oxazolines serve as active donors for iterative synthesis of type I oligosaccharides - Verma, Nitish; Tu, Zhijay; Renata, Septila; Lin, Chun-Hung (Chemical communications (Cambridge, England), 2024)
Synthesis of Galβ1 → 3GlcNAc-repeating saccharides is limited mainly by the formation of less-reactive oxazolines. We herein report an expeditious approach that requires trichloroacetyloxazolines as reactive glycosyl donors. Using only two disaccharide building blocks, the iterative oxazoline formation and glycosylation synthesized hexa- and octasaccharides with overall yields of 47% and 26% in four and six steps, respectively. Oxazoline-based iterative glycosylation to synthesize hexa- and octasaccharides in an expeditious manner.